Prognosis prediction of α-FAtE score for locoregional immunotherapy in hepatocellular carcinoma - Zheng, Zehao; Guan, Renguo; Zhao, Rongce; Gan, Junyu; Xiong, Xinhao; Zou, Jing-wen; Li, Shaohua; Wang, Qiaoxuan; Wei, Wei; Mei, Jie; Guo, Rongping (Frontiers in Immunology, 2025)
PurposeThe α-FAtE score, composed of alpha-fetoprotein, alkaline phosphatase, and eosinophil levels, has been reported as a predictor of prognosis in hepatocellular carcinoma (HCC) patients treated with atezolizumab plus bevacizumab. This study aimed to investigate the predictive ability of α-FAtE score for the efficacy and safety of locoregional immunotherapy as the treatment of HCC patients.Methods and patientsWe conducted a retrospective study of 446 HCC patients at Sun Yat-sen University Cancer Center from January 1st 2019 to January 1st 2023. The predictive performance was evaluated by the concordance index, the area under the receiver operating characteristics curve, the Kaplan-Meier curve and multiple Cox regression analysis.Results446 patients were divided into the α-FAtE 0-1 group (n=211) and α-FAtE 2-3 group (n=235). The median progression-free survival(PFS) of the α-FAtE 0-1 group and 2-3 group was 7.3 months (95%CI 6.6-8.7 months), and 12.3 months (95% CI 10.4–14.1 months; P<0.001), respectively. The median overall survival (OS) of the α-FAtE 0-1 group and 2-3 group was 16.3 months (95%CI 13.7-21.5 months) and 34.1 months (95% CI 27.6–NA months; P<0.001), respectively. HCC patients in the α-FAtE 2-3 group had higher complete response (CR) rate and experienced less drug-related adverse events than those in the α-FAtE 0-1 group. Moreover, a lower α-FAtE score was identified as an independent prognostic indicator for both OS and PFS of advanced HCC patients receiving locoregional immunotherapy.ConclusionThe α-FAtE score is a superior predictor of prognosis in HCC patients receiving locoregional immunotherapy, offering a valuable tool for patient stratification and treatment planning.